EFFECT OF PROFIT MANAGEMENT ON ANNUAL REPORT READABILITY - Elfina Astrella Sambuaga; Kezia Algise Iksanto; Natasha Emmanuela; N.P. Qintari M.Y. (Jurnal Akuntansi Bisnis, 2022)
ABSTRACT : This study examines the effect of earnings management to annual report readability. This study uses data from the non-financial sector of companies listed on the Indonesia Stock Exchange (BEI) for the period (2014-2018) with a total of 825 observations. The data collection technique uses purposive sampling and data analysis uses multiple regression analysis methods. Based on the results of the research on the first hypothesis, an increase in income reflects earnings management which negatively affects the annual report readability, while the results of the second and third hypotheses are an increase in income and discretionary accruals as well as an increase in income and discretionary accruals above the median, both of which simultaneously reflect earnings management that are not significantly influence the annual report readabilityKeywords: earnings management, annual report readability, discretionary accruals ABSTRAK : Tujuan penelitian ini untuk menguji pengaruh manajemen laba terhadap keterbacaan laporan tahunan dengan menggunakan data sektor non-keuangan perusahaan yang terdaftar di Bursa Efek Indonesia (BEI) periode (2014-2018). Total observasi yaitu 825, dengan menggunakan teknik pengumpulan data menggunakan purposive sampling dan analisis data memakai metode analisis regresi berganda. Hasil penelitian menunjukkan bahwa peningkatan pendapatan mencerminkan manajemen laba yang berpengaruh negatif terhadap keterbacaan laporan tahunan, sedangkan hasil hipotesis kedua dan ketiga yaitu peningkatan pendapatan dan discretionary accruals serta peningkatan pendapatan dan discretionary accruals di atas median, keduanya secara bersamaan mencerminkan manajemen laba yang tidak berpengaruh secara signifikan terhadap keterbacaan laporan tahunan.Kata Kunci: manajemen laba, keterbacaan laporan tahunan, discretionary accruals